Restoring the “Nusantara”: Integration of historical values and modern logistics policy - Budi Purwanto; Annisa Pangestuti; Moch Alfian Eko Prasetyo (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study aims to examine the significance of achieving logistical objectives across different economic eras and to identify how historical maritime values can improve modern logistics systems. The research represents the author’s perspective, combining field experience and previous studies through a qualitative descriptive approach and a cross-checked literature review. The findings indicate that ancient maritime civilizations practiced a more holistic, integrated logistics system than contemporary logistics, which is fragmented. Therefore, the concept of logistics restoration is proposed as a strategic approach to reintegrate historical values into modern logistics practices by leveraging information technology, service networks, managerial strategies, and cultural adaptation. This study integrates literature-based analysis and empirical insight to emphasize the importance of institutional integration—both at the corporate and national levels—in establishing an efficient, collaborative, and sustainable logistics ecosystem.